Depth of insertion of a lumbar puncture needle. Issue 5 (1st November 1997) - Craig, F; Stroobant, J; Winrow, A; Davies, H
Abstract : The depth of lumbar puncture needle insertion was recorded in 107 children. Height provided the best guide to the minimum and maximum depths of insertion. Mean depth of insertion (cm) = 0.03 × height of child (cm).